2003
DOI: 10.1128/jb.185.16.4938-4947.2003
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of a Bactericidal Domain of Puroindoline a: Structure and Mechanism of Action of a 13-Residue Antimicrobial Peptide

Abstract: Puroindoline a, a wheat endosperm-specific protein containing a tryptophan-rich domain, was reported to have antimicrobial activities. We found that a 13-residue fragment of puroindoline a (FPVTWRWWKWWK G-NH 2 ) (puroA) exhibits activity against both gram-positive and gram-negative bacteria. This suggests that puroA may be a bactericidal domain of puroindoline a. PuroA interacted strongly with negatively charged phospholipid vesicles and induced efficient dye release from these vesicles, suggesting that the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 68 publications
9
104
0
Order By: Relevance
“…The cationic charges of arginine provide an effective means of attracting with negative charged surfaces such as LPS, teichoic acid, or phosphatidyl glycerol phospholipids head group. Moreover, arginine can form a complex with tryptophans via cation-interaction which is favourable to penetrate into a lipid bilayer (Jing et al, 2003). The difference in arginine content may be responsible for high antimicrobial activity of dLz.…”
Section: Resultsmentioning
confidence: 99%
“…The cationic charges of arginine provide an effective means of attracting with negative charged surfaces such as LPS, teichoic acid, or phosphatidyl glycerol phospholipids head group. Moreover, arginine can form a complex with tryptophans via cation-interaction which is favourable to penetrate into a lipid bilayer (Jing et al, 2003). The difference in arginine content may be responsible for high antimicrobial activity of dLz.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the RWxxW motif found in the lysis protein E is also observed close to the N-or C-terminus of several naturally occurring cationic antimicrobial peptides, including indolicidin [51], cecropin [52], tritrpticin [53], lactoferricin B [54], and puroindoline A [55] as shown in Table 2. Many synthetic variants of cationic antimicrobial peptides have been generated by Hancock and co-workers, who have observed that Arg and Trp predominate in high activity peptide sequences [56][57][58], including that of clinical candidate MX226 (Omiganan) [57].…”
Section: A Novel Site Of Action For Cationic Antimicrobial Peptides Cmentioning
confidence: 98%
“…The preferential location of W residues at the membrane interface has been attributed to their aromaticity and ability to form hydrogen bonds with both water and polar lipid headgroup moieties [58,63,136,137,140,141]. In this study, hydrophobicity and highly membrane active -helical CAPs, were used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influence of dipole and quadrupole moments became apparent in intramolecular interactions between the -electrons of the indole ring of W with the positively charged guanidino moiety of R in RW-rich peptides, which were suggested to stabilize the structure of CAPs and enhance membrane binding [136,137]. Because of the higher quadrupole moment (aromaticity) of the indole ring in c-(5MeoW)F(5MeoW) compared with c-(5fW)F(5fW) [124], a higher affinity of the former peptide for lipid bilayers was expected [136,137]. However, the opposite was observed ( Fig.…”
Section: Role Of Sequence Composition Upon Bindingmentioning
confidence: 99%